Innovation and Performance of Small and Medium-sized Bakeries in Tanzania - Jeje, Kafigi (Acta Universitatis Danubius. Œconomica, 2022)
Small and Medium-sized Enterprises in Tanzania are still facing numerous challenges that have been affecting their competitiveness. To a great extent, literature has confirmed that innovation is a major driver of their competitiveness. One of the major challenges facing the owners or managers of these enterprises is the failure to understand and employ the right innovation strategies that can drive their performance. The performance of SMEs has a significant contribution to the socioeconomic development of many economies such as Tanzania where agriculture is one of the leading sectors. Enabling direct or indirect players in the agriculture sector such as the food enterprises, impacts the economy. We therefore characterise innovation as enhanced innovation process, customer-focused innovation, and enhanced innovation environment, and find whether they influence sales, and output performance of small and medium-sized bakeries. Our study adopts a multi-stage sampling technique and received responses from 161 questionnaires, and 20 in-depth interviews from bakery owners/managers throughout Tanzania. Through a moderator analysis, we find that both human resource competency and the size of the bakery moderate the relationship between innovation strategies and bakery performance. We argue that SMEs need to enhance their innovation capabilities in order to compete. Nevertheless, such capabilities should be supported by the innovation commitment of SMEs, and the policy development practices in the internal and external business environments.